Chapter 5 Mercury Tonics (Rasāyana) in Sanskrit Medical Literature - Wujastyk, Dagmar (Equinox, 2016)
This chapter will provide a brief survey of the uses of mercury preparations in rasāyana therapy, discussing their position within rejuvenation therapy in regard to other rasāyana formulations and exploring their link with Indian alchemical traditions.